Level Analysis of Palangka Raya University Building Damage - Lisa Wati; Puspasari, Veronika Happy; Gawei, Apria Brita Pandohop (PT Mattawang Mediatama Solution, 2022)
The lecture building is the same building as the building in general, namely a building made of wood or concrete construction. During its operation, the potential for damage to an old building or a relatively newly constructed building is very large. There is no data on damage at the University of Palangka Raya that has caused a decrease in the level of productivity of activities carried out by building owners or users so that the condition of the college building is not well maintained. This research was conducted by conducting a survey of filling out the form in the building of the first lecture building of the Faculty of Economics and Business, University of Palangka Raya. The survey form was analyzed further, 3 categories of component types emerged, namely Architectural: Foundations, Sloof, Columns, Ring Balk, Walls, and Roof Frames, Architectural: Roofs, Ceilings, Floors, Locks, Frames and Leaves, as well as Painting, Utilities: MCK, and Electrical: Electric. The analysis used is descriptive analysis. The results of this analysis show that 3 components, which have a percentage damage of 0.5% of keys, 0.7% of frames and leaves, and 7.37% of painting, with a total of 8.6% fall into the category of damage levels, namely lightly damaged, with a budget of Rp. 759.736.00 for keys, Rp. 3,495.992.39 for frames and leaves, and Rp. 106.463.066.64 for painting, with a total cost of damage of Rp. 110,718,795.02. This research is useful for managers and further research can be a reference in improving the quality of the building.